Karakteristik Fisikokimia dan Sensori Mi dengan Substitusi Tepung Kentang - Ria Noviar Triana; Nuri Andarwulan; Dede Robiatul Adawiyah; Denny Agustin; Rini Kesenja; Desty Gitapratiwi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
Noodles are made from wheat flour, starch, water salt, and other ingredients that improve the texture and flavor of noodles. The objectives of this research were: (1) characterize of dough made using potato flour, (2) characterization physicochemical and sensory characteristics of noodles as affected by potato flour as substituent of wheat flour. The use of potato flour is expected to improve quality of noodles produced either from sensory properties as well as its functional properties. Process for making noodle with potato flour substituted includes mixing (10 minute), resting (5 minute), sheeting (9-13 time), slitting, cutting, steaming (10 minute, 100 °C) and drying (90 minute, 70°C, dried noodles) or frying (1-1.5 minute, 160°C, fried noodles). Good noodle dough can be produced relatively easy if level of substitution by potato flour were not more than 10% (fine flour), 25% (granule), 15% (ground standard flakes), and 5% (standard flakes). Wet noodles subtituted by potato flour had smooth of mouthfeel, addition of potato flour in dried noodles can improve attribute sweet potato aroma, more easy dehydrated and a lower moisture content, while fried noodles subtituted by potato flour produce quite strong attribute sweet potato aroma, improve the taste and lower moisture content.